Analysis of the epidemiological characteristics of neurosyphilis in Tianjin Huanhu Hospital from 2012 to 2017 - Wen-yue WANG (Chinese Journal of Contemporary Neurology and Neurosurgery, 2019)
Objective To analyze the epidemiological characteristics of neurosyphilis in Tianjin Huanhu Hospital. Methods The epidemiological data, laboratory examination results and neuroimaging features of 138 patients with neurosyphilis who were diagnosed and treated in our hospital from 2012 to 2017 were retrospectively analyzed. Results All patients were divided into asymptomatic neurosyphilis (asymptomatic group, N = 32), interstitial neurosyphilis (interstitial group, N = 46) and parenchymatous neurosyphilis (parenchymatous group, N = 60). The proportion of male patients (χ2 = 9.623, P = 0.002; χ2 = 7.953, P = 0.005) and age (t = 2.985, P = 0.004; t = 3.322, P = 0.001) of parenchymatous group were higher than those of asymptomatic group and interstitial group. The rapid plasma reagin (RPR) titers of interstitial group (Z = 2.394, P = 0.024) and parenchymatous group (Z = 2.937, P = 0.004) were higher than that of asymptomatic group. The protein quantification of parenchymatous group was higher than that of asymptomatic group (t = 2.453, P = 0.017). The imaging findings of patients in asymptomatic group showed no abnormalities. The imaging findings of 22 patients in interstitial group showed cerebral infarction, while the other one did not show abnormality. The imaging findings of 28 patients in parenchymatous group showed abnormalities such as cerebral ischemia, white matter degeneration, demyelination and hydrocephalus, while the other 7 patients did not show abnormality. Conclusions Neurosyphilis is more common in men and lower education people, which has complex and diverse clinical features and imaging manifestations. It is necessary to strengthen the measures of health education and behavior intervention in high-risk population, so as to reduce the incidence of neurosyphilis.